ПЕДАГОГИЧЕСКИЕ ПОДХОДЫ К ОБУЧЕНИЮ САМОКОНТРОЛЮ И САМООРГАНИЗАЦИИ В ШКОЛЕ ДИАБЕТИКОВ - Курбанов Дониёр Бахтиёрович; Зокирова Мохирабону Махмуджон кизи; Тургунова Фотима Акбарали кизи 3; Исмоилова Севинч Муродбек кизи; Жамолиддинов Нурмухаммад Жалолиддин оглы (TADQIQOTLAR, 2025)
Abstract. This review is an analysis of available data on pedagogical approaches that are effective for implementation and use in educational programs for people with diabetes. This topic is both interesting and relevant because, unfortunately, the number of  people  suffering  from  diabetes  is  growing,  and  there  are  very  few  educational programs for patients to improve their quality of life, and they are not as widespread as one would hope. Through our analysis and study of published scientific works, we aim to help research institutes (RIs), higher medical educational institutions (medical universities), and medical and preventive institutions (MPIs) to organize an educational and medical platform aimed at developing self-control skills in patients with diabetes mellitus. To study this topic, we used modern evidence-based medicine databases such as PubMed, ScienceDirect, BMC Nursing, and PMC. We did not limit our search to Russian-language sources, but also studied articles in English. As a result, we provided a  general  overview  for  those  who  are  not  familiar  with  such  medical  educational programs and several highly effective pedagogical approaches to teaching self-control and self-organization in diabetes schools.